Reduced peroxisome proliferator-activated receptor-α and bile acid nuclear receptor NR1H4/FXR may affect the hepatic immune microenvironment of biliary atresia - Ma, Yingxuan; Lu, Li; Tan, Kezhe; Li, Zhi; Guo, Ting; Wu, Yibo; Wu, Wei; Zheng, Lulu; Fan, Feilong; Mo, Jiayu; Gong, Zhenhua (Frontiers in Immunology, 2022)
Background:Biliary atresia (BA) is a childhood liver disease characterized by fibrous obstruction and obstruction of the extrahepatic biliary system and is one of the most common and serious biliary disorders in infants.Significant inflammation and fibrosis of the liver and biliary tract are the most prominent features, regardless of the initial damage to the BA.Abnormalities in innate or adaptive immunity have been found in human patients and mouse models of BA.We previously reported that children with BA had abnormal lipid metabolism,including free serum carnitine. Objective:To study gene and protein expression levels of the hepatic peroxisome proliferator-activated receptor-α (PPARα) signaling pathway and farnesoid X receptor (FXR) in BA. Methods:Low expression of PPARα and NR1H4 (FXR) in BA were validated in the Gene Expression Omnibus database. Functional differences were determined by gene set enrichment analysis based on of PPARα and NR1H4 expression. BA patients from GSE46960 were divided into two clusters by using consensus clustering according to PPARα, NR1H4, and SMAD3 expression levels, and immunoinfiltration analysis was performed. Finally, 36 cases treated in our hospital were used for experimental verification. Results: Bioinformatics analysis showed that the expression of PPARα, CYP7A1 and NR1H4 in the biliary atresia group was significantly lower than in the control group. More BA-specific pathways, including TGFβ signaling pathway,etc., are enriched in BA patients with low PPARα and NR1H4 expression. In addition, low NR1H4 expression is abundant in inflammatory responses, IL6 / STAT3 signaling pathways, and TGFβ signaling pathways. The TGFβ signaling pathway was significant in both groups. According to the expression of PPARα, NR1H4 and SMAD3, a key node in TGFβ pathway, BA patients were divided into two clusters using consensus clustering . In cluster 2, SMAD3 expression was high, and PPARα and NR1H4 expression were low. In contrast to cluster 1, immune cell infiltration was higher in cluster 2, which was confirmed by immunohistochemistry. The mRNA and protein levels of PPARα and NR1H4 in BA patients were lower than in the control group by immunohistochemistry, Western blot analysis and real-time PCR. Conclusions: The downregulation of PPARα and NR1H4 (FXR) signaling pathway may be closely related to biliary atresia.